Dynamic profile of differentiated thyroid cancer in male and female patients with thyroidectomy during 2000–2013 in China: a retrospective study. Issue 1 (December 2017) - Yan, Hui-xian; Pang, Ping; Wang, Fu-lin; Tian, Wen; Luo, Yu-kun; Huang, Wei; Yang, Guo-qing; Jin, Nan; Zang, Li; Du, Jin; Ba, Jian-ming; Dou, Jing-tao; et al.
Abstract The study aimed to investigate the gender-related differences of disease onset, age distribution, blood type, clinical characteristics, and malignant behaviors of differentiated thyroid carcinoma (DTC) in Chinese patients. A total of 7385 consecutive thyroid cancer patients who underwent thyroidectomy were retrospectively reviewed. 4087 (55.3%) were diagnosed as benign and the other (3298, 44.7%) were as malignant. DTC accounted for 97.6% in the malignant tumor. More single nodules turned out to be DTC in male compared to multiple nodules (46.9% vs. 40.4%, P = 0.004). The proportion increased along with the increase of year during 2000–2013, which was from 7.5% to 68.1% in males and from 16.2% to 66.7% in females. The level of preoperative TSH was significantly higher in patients with DTC compared to the patients with benign (1.97 vs. 1.57 mIU/L, P < 0.001). The proportion of thyroid cancer was dominated in blood type B and the lowest incidence in blood type A in male, the difference was not statistically significant. The results showed that age, nodule number, BMI and serum TSH were the related factors for DTC. More aggressive behaviors of DTC were observed in male patients, and more attention should be focused on the timely diagnosis and treatment of these patients.